2010
DOI: 10.1080/03004430903414703
|View full text |Cite
|
Sign up to set email alerts
|

Fathers’ frightening behaviours and sensitivity with infants: relations with fathers’ attachment representations, father–infant attachment, and children’s later outcomes

Abstract: This longitudinal study of 125 families investigated whether negative child outcomes related to fathers' frightening (FR) behaviours with infants would be mitigated if fathers were also sensitive. Results indicated that children whose fathers were frightening and insensitive with them during infancy showed the highest emotional under-regulation at 24 months and highest teacher ratings of attention problems at age 7, whereas those whose fathers were frightening and sensitive did not differ from children whose f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
2
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 17 publications
(27 reference statements)
2
62
2
4
Order By: Relevance
“…Whereas mothers may socialize children primarily in the context of caregiving, fathers may do so primarily in the context of play (Umemura, Jacobvitz, Messina, & Hazen, 2013). Fathers often arouse their child's emotions when playing and then help calm the child down (Hazen, McFarland, Jacobvitz, & Boyd-Soisson, 2010), which may provide practice in emotional regulation for infants and toddlers (Grossmann, Grossmann, Fremmer-Bombik, Kindler, & Scheuerer-Englisch, 2002). Thus, if fathers respond to infant negative emotion with distressed responses, this could be particularly dysregulating, leading to greater toddler negative or flat/withdrawn affect.…”
Section: Parents' Distressed Responses To Infants' Negative Emotionsmentioning
confidence: 94%
“…Whereas mothers may socialize children primarily in the context of caregiving, fathers may do so primarily in the context of play (Umemura, Jacobvitz, Messina, & Hazen, 2013). Fathers often arouse their child's emotions when playing and then help calm the child down (Hazen, McFarland, Jacobvitz, & Boyd-Soisson, 2010), which may provide practice in emotional regulation for infants and toddlers (Grossmann, Grossmann, Fremmer-Bombik, Kindler, & Scheuerer-Englisch, 2002). Thus, if fathers respond to infant negative emotion with distressed responses, this could be particularly dysregulating, leading to greater toddler negative or flat/withdrawn affect.…”
Section: Parents' Distressed Responses To Infants' Negative Emotionsmentioning
confidence: 94%
“…Bu dönemde bebekler acıktıklarında ve yorulduklarında annelerini, aktif oldukları oyun zamanlarında ise babalarını tercih etmektedirler. 20,21 Babalar annelere göre bebekleriyle daha çok oyun faaliyetleriyle meşguldür ve daha az bakım verme rolünü üstlenirler. Primer olarak anneler bebeklerin bakımlarını üstlenir ve onlara her an ulaşabilecek yakınlıktadırlar.…”
Section: Baba-bebek Bağlanmasinin Farkliliklariunclassified
“…Bunun gerçekleşmesinde, bebeğin algıları da etkilidir. 20,21 Bağlanma konusunda, annenin etkisi kabul edilen bir gerçektir. Dolayısıyla baba-bebek bağ-lanmasını belirleyen en önemli koşul, anne-babanın iletişim biçimidir.…”
Section: Anneni̇n Etki̇si̇unclassified
See 1 more Smart Citation
“…When infants and toddlers are content, they may seek interaction from either caregiver. Previous studies have found that fathers often engage in physically stimulating and unpredictable play (ClarkeStewart, 1978;Hazen, McFarland, Jacobvitz, & Boyd-Soisson, 2010;Paquette, 2004;Power & Parke, 1983;Teti, Bond, & Gibbs, 1988). For example, fathers tend to provide staccato bursts of both physical and social stimulation to their newborn infants whereas mothers tend to be more rhythmic and containing (Yogman, 1981).…”
Section: The Role Of Emotion In Children's Preferencesmentioning
confidence: 99%